Sensor array current consumption optimizer with Gradient Descent - Shabanski, Boyan Y. (2023 XXXII International Scientific Conference Electronics (ET), 2023)
This article aims to show an example realization of Gradient descent algorithm for power supply consumption optimization in embedded sensor systems by means of adjusting measurement cycles to meet a given user target input. When execution is complete, the tool returns measurement cycle information that satisfy the given user target for overall current consumption. Example implementation is done in Python.